A high-performance hardware architecture of an image matching system based on the optimised SIFT algorithm - Deng, Wenjuan (2014)
The Scale Invariant Feature Transform (SIFT) is one of the most popular matching algorithms in the field of computer vision. It takes over many other algorithms because features detected are fully invariant to image scaling and rotation, and are also shown to be robust to changes in 3D viewpoint, addition of noise, changes in illumination and a sustainable range of affine distortion. However, the computational complexity is high, which prevents it from achieving real-time. The aim of this project, therefore, is to develop a high-performance image matching system based on the optimised SIFT algorithm to perform real-time feature detection, description and matching. This thesis presents the stages of the development of the system. To reduce the computational complexity, an alternative to the grid layout of standard SIFT is proposed, which is termed as SRI-DASIY (Scale and Rotation Invariant DAISY). The SRI-DAISY achieves comparable performance with the standard SIFT descriptor, but is more efficient to be implemented using hardware, in terms of both computational complexity and memory usage. The design takes only 7.57 µs to generate a descriptor with a system frequency of 100 MHz, which is equivalent to approximately 132,100 descriptors per second and is of the highest throughput when compared with existing designs. Besides, a novel keypoint matching strategy is also presented in this thesis, which achieves higher precision than the widely applied distance ratio based matching and is computationally more efficient. All phases of the SIFT algorithm have been investigated, including feature detection, descriptor generation and descriptor matching. The characterisation of each individual part of the design is carried out and compared with the software simulation results.